BOOK REVIEW: Martin Dojčár, ‟Spirituálny dialóg” [‟Spiritual Dialogue”], Trnava, Faculty of Theology, University of Trnava, 2021, 118 p. - DANCÁK, Pavol (Studia Universitatis Babeș-Bolyai Theologia Catholica, 2022)
Together with the pluralistic paradigm of postmodern culture, the fundamental ethical question of moral justification has resurfaced again. In the postmodern context, it is necessary to rethink the need to interiorize values of a moral nature, especially those concerning the way of life of both the individual and community and consequently also the interpersonal coexistence. Doctor Martin Dojčár’s monograph offers a synthesis of his decade-long committed research into a spiritual dialogue as a new and highly relevant form of interreligious dialogue. The author presents to the reader this fascinating form of dialogue. He does so not only through a thorough review of the vast body of scholarly literature, but mainly through his own experience with it on an interpersonal and intra-spiritual level.